Rekrutmen PDIP dalam Pilkada 2020: Antara Strategi Pemenangan dan Pelembagaan Partai Politik - Joko J Prihatmoko (Universitas Wahid Hasyim Semarang, 2022)
This paper describes the winning strategy and institutionalization of political parties in the recruitment of PDIP candidates in 21 districts/cities in the 2020 simultaneous regional head and deputy regional head elections in Central Java Province. The research uses a literature study method with a qualitative approach. The results showed that the recruitment of PDIP candidates in the simultaneous regional head elections was capitalized as part of a winning strategy rather than party institutionalization. Using Adman Nursal's concept, found 7 recruitment patterns, which are based on four strategies: a) reinforcement, b) rationalization, c) inducement, and d) confrontation.From the point of view of party institutionalization based on the concept of Vicky Randall and Lars Svasand, it can be seen that the magnitude of the push as a floating party is indicated by the degree of (1) systemness, (2) value identity, (3) autonomy in decision making, and (4) knowledge or public image (reification) of a political party.The pattern of PDIP regional election recruitment that is closed but seems open confirms the development of the character of a “floating party”, namely a political party that is less responsible and less responsive to its constituents. Luckily, in a floating mass atmosphere that is not politically literate, PDIP candidates won the majority of the 2020 simultaneous regional elections in Central Java.Keywords: Political Recruitment, Winning Strategy, Political Institutionalization, Floating PartyAbstrakPenelitian ini ingin menjelaskan strategi pemenangan dan pelembagaan partai politik dalam rekrutmen calon PDIP di 21 kabupaten/kota pada pemilihan kepala daerah dan wakil kepala daerah serentak tahun 2020 di Provinsi Jawa Tengah. Penelitian menggunakan metode studi kepustakaan dengan pendekatan kualitatif. Hasil penelitian menunjukkan rekrutmen calon PDIP pada pilkada serentak dikapitaliasi sebagai bagian strategi pemenangan dibanding pelembagaan partai. Menggunakan konsep Adman Nursal, ditemukan 7 pola rekrutmen, yang didasarkan pada empat strategi: a) penguatan (reinforcement strategy), b) rasionalisasi (rationalization strategy), c) bujukan (inducement srategy), dan d) konfrontasi (confrontation strategy). Dari sudut pelembagaan partai berdasarkan konsep Vicky Randall dan Lars Svasand terlihat besarnya dorongan sebagai partai mengambang (floating party) yang diindikasikan dari derajat (1) kesisteman (systemness), (2) identitas nilai (value infusion), (3) otonomi dalam pembuatan keputusan (decisional autonomy), dan (4) pengetahuan atau citra publik (reification) terhadap suatu partai politik. Pola rekrutmen pilkada PDIP yang tertutup tapi terkesan terbuka mengkonfirmasikan terbangunnya watak “partai mengambang” (floating party), yakni partai politik yang kurang bertanggungjawab dan kurang tanggap terhadap konstituen. Beruntung, dalam atmosfer massa mengambang (floting mass) yang tidak melek politik, calon-calon PDIP memenangi mayoritas pilkada serentak tahun 2020 di Jawa Tengah.Kata Kunci : Rekrutmen Politik, Strategi Pemenangan, Pelembagaan Politik, Partai Mengambang